QRIS in the Vortex of Financial Innovation: A Bibliometric Approach - Ula, Indah Syafa'atul; Rosalina, Rita (Library of Sultan Agung Islamic University, 2025)
QRIS (Quick Response Indonesian Standard) has become one of the main financial innovations in Indonesia, facilitating efficient and standardized cashless digital transactions. Since its launch in 2019, QRIS has experienced significant growth in user adoption, especially amid the COVID-19 pandemic, which accelerated the shift towards contactless payments. This study uses a bibliometric approach to analyze literature related to QRIS, mapping research trends, collaborations, and factors influencing the adoption and acceptance of this technology in Indonesia. Based on data obtained from Scopus (2019-2025), this study identifies a significant increase in publications discussing QRIS, especially those related to implementation challenges, social impacts, and supportive policies. This study also applies the Diffusion of Innovations (DOI) theory to explain the QRIS adoption process, focusing on perceived ease of use, perceived benefits, and social attitudes towards the technology. The results of the analysis show that although QRIS has been well received by consumers and business actors, there are still barriers to adoption by small and medium enterprises (SMEs). This research provides important insights for policy makers and industry players in formulating strategies to accelerate the spread of QRIS and encourage financial inclusion in Indonesia.